Extended-spectrum beta-lactamase-producing Klebsiella pneumoniae in paediatric wards: A nested case-control study - KARAHASAN, AYŞEGÜL (BLACKWELL PUBLISHING, 2008)
Aim: A high rate (48.6%) of extended spectrum beta-lactamase production among Klebsiella pneumoniae (ESBL-KP) clinical isolates in the paediatric wards of our hospital prompted the introduction of enhanced infection control measures, and after the implementation of these measures, we instituted a prospective surveillance programme, with a nested case-control study to determine the risk factors for rectal colonisation by ESBL-KP. Methods: Over a 1-year period, rectal swabs from patients and samples from the environment and the hands of health-care workers were cultured. Strain typing of ESBL-KP isolates was performed using pulsed-field gel electrophoresis. Characteristics of patients who were colonised with ESBL-KP during hospital stay were compared with those of patients who remained negative for ESBL-KP. Multivariate analysis was performed with model-building using stepwise logistic regression to determine independent risk factors for ESBL-KP acquisition. Results: Forty (18.5%) of 216 patients became colonised with ESBL-KP. The strongest independent predictors of ESBL-KP colonisation were mechanical ventilation (odds ratio (OR): 4.28) and hospitalisation for longer than 14 days (OR: 6.97). Genotyping of the isolates indicated probable patient-to-patient transmission; however, we could not determine the route of this spread. During the study period, a 1.6% rate of ESBL-KP clinical infection per 500 patient admissions was observed, in contrast to a 7% rate in the previous year. Conclusions: Prolonged length of stay and mechanical ventilation were independent predictors of ESBL-KP colonisation. Enhanced infection control measures, antimicrobial stewardship and screening for rectal carriage were associated with a substantial decrease in paediatric units.
Keywords: beta lactamase; infection control; Klebsiella pneumoniae; INTENSIVE-CARE-UNIT; RISK-FACTORS; TRANSFERABLE RESISTANCE; COLONIZATION; OUTBREAK; EPIDEMIOLOGY; PREVALENCE; INFECTION; CARRIAGE; STRAINS